Simulasi Antena Microstrip Transparan Pada Frekuensi 5.8 Ghz Untuk Advance Traffic Management System (ATMS) - Ramadoni Ramadoni; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Microstrip transparent antenna investigated and optimized for a vehicular communication system, facilitating vehicle-to-vehicle and vehicle to roadside communication. The antenna operated at frequency of 5.8 GHz with the substrate used is glass Aght-4. This paper presents the simulated antenna with panthom using software CST Microwave Studio. From the simulation the results obtained are gain of 4.33 dBi with directional radiation - pattern at frequency 5.8 Ghz. Keywords: Advanced Traffic Management System, Microstrip Antenna Transparent.